eCommerce and Tourism: Leveraging on University-Community Collaboration for Socio-economic Development of Indigenous Communities in Sarawak - Tariq, Zaman; Ngo, June Siok Kheng; Phoa, J.; Alvin Wee, Yeo (2016)
With many Indigenous people living in remote communities, opportunities for traditional face-to-face commerce are extremely limited. Even in urban centres, the cost of setting up bricks-and-mortar shopfronts limits business prospects for many indigenous people, despite the high demand and high prices customers are prepared to pay for their art, crafts and cultural tourism services. As a consequence, many indigenous communities of Sarawak have in the past been subject to massive exploitation by non-indigenous middlemen, who have paid the crafts person little for their work and then enjoyed huge profits themselves. The Institute of Social Informatics and Technological Innovations (ISITI) has been working together with the Penan community in Long Lamai since 2009 to set up infrastructure and telecommunications in their rural village. Identifying the problems such as rural-urban migration and the need to improve the social economic status of Penans in Long Lamai, ISITI obtained grants to develop an eCommerce eco-system for the community. The website serves as an online platform to promote their homestay and to sell Penan handicrafts to the outside of Long Lamai. However during the two years of the project, other issues have transpired due to new aspects, which had to be taken account. In this paper, we are sharing experience, challenges and lesson learned of our long term partnership project with the local communities of Sarawak. The research findings will help researchers to better understand the structure of economic activities in indigenous communities and then use this understanding for designing better solutions for addressing social and economic problems in indigenous communities.